The Relationship between Principal Authentic Leadership and Teacher Knowledge Sharing: An Empirical Analysis Based on the Self-Determination Theory - Zhang, Wanying (Best Evidence in Chinese Education, 2025)
Teacher knowledge sharing is a process in which teachers collaborate to boost their understanding and construction of knowledge by integrating fragmentary knowledge owned by individuals into a shared knowledge system. It helps promote common development in teachers as well as enhance the school’s quality of knowledge base as an educational community. Nevertheless, the teacher may tend to keep their knowledge private to maintain their professional distinctiveness. Also, educational and instructional expertise is often interwoven into the education process, and its implicit nature is an impediment to its sharing. Hence, teacher knowledge sharing has become a pronounced issue in modern school management. Recent research in this area reveals that the principal leadership style has a significant impact on the teachers’ knowledge sharing behavior. This study investigates the relationship between principal authentic leadership and teacher knowledge sharing, as well as its influencing factors, from the perspective of the self-determination theory.